Learning Social Skills and Accruing Social Capital through Pervasive Gaming - Sampsa Rauti; Samuli Laato; Tarja Pietarinen (My University, 2022)
There are several implicit benefits to formal school education. One the most important is the learning of social skills i.e. how to behave, interact meaningfully and form social bonds with other people. However, there are multiple situations where the learning of social skills can be disrupted, e.g. bullying or the recent COVID-19 pandemic that forced schools to transition into distance education. In this work, we investigate the potential of pervasive games (PGs) to teach social skills and help acquire social capital. Using the theoretical viewpoints of affordance lens and Pierre Bourdieu's theory of capital, we argue that PGs are able create meaningful activities that not only help learn social skills, but can scaffold social bonding and increase social capital. We identify six social affordances in the PG Pokémon GO and show the game teaches a wide variety of social skills ranging from negotiation and bartering to group interaction. Our findings have implications on designing educational pervasive games that teach social skills and accrue social capital. Keywords: pervasive games, implicit learning, social capital, social capital theory, social skills.
Proceedings of DELbA 2020 - Workshop on Designing and Facilitating Educational Location-based Applications co-located with the Fifteenth European Conference on Technology Enhanced Learning (EC-TEL 2020)